Arhitekturna vsebina med abstraktnim in konkretnim - Marolt, Peter (AR. Arhitektura, raziskave, 2005)
The article presents methods of non-verbal communication and architectural expression as methods of artistic communication. Methods of non-verbal communication evolved in conjunction with consciousness, scientific and progress, cultural setting. By using "images" and "sight they led to improved methods of communication, indirectly leading to complex architectural representation with architectural plans in the forefront. Even an architectural plan is a method of non-verbal communication, similar to a sketch or any form of representing architectural space. When the form of representing a building points out the ontological essence of its layout and expresses its identity to the extreme, when the source, structure of the idea and cognitive model are shown, when such representation implies transformation of the visual (and tactile) world into pure abstract form, then we speak about the form of (representing architectural space as) an ideogram, above all we thus confirm the link between architecture and other types of fine arts.
Keywords: architecture; arhitektura; arhitekturni prostor; arhitekturna vsebina; likovna komunikacija